2012
DOI: 10.1038/eye.2012.216
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer and optic disc measurements by spectral domain OCT: normative values and associations in young adults

Abstract: Purpose To determine normative values and associations of retinal nerve fiber layer (RNFL) and optic disc parameters in normal eyes measured by spectral domain optical coherence tomography (OCT).Methods In a population-based setting, 1521 young adults were examined as part of the Sydney Adolescent Vascular and Eye Study (SAVES). Their mean age was 17.3 ± 0.6 years. RNFL and optic disc parameter measurements were made using Cirrus HD-OCT 4000. Results The average RNFL was found to be 99.4±9.6 lm. RNFL thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 44 publications
6
38
1
6
Order By: Relevance
“…Except for Latinos over 70 years of age, 20 two Indian studies, 35,36 a study in China 42 and Europe 21 which have reported that the RNFL is thickest in the superior quadrant, other studies are in agreement with us that the inferior quadrant has the thickest RNFL. Also, our results are in line with most studies stating that RNFL is thinnest in the temporal quadrant; 20,45 while a few studies report it to be nasal. 46,47 RNFL thickness is believed to correspond with the physiologic neuroretinal rim shape which follows the Inferior-Superior-Nasal-Temporal (ISNT) rule.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Except for Latinos over 70 years of age, 20 two Indian studies, 35,36 a study in China 42 and Europe 21 which have reported that the RNFL is thickest in the superior quadrant, other studies are in agreement with us that the inferior quadrant has the thickest RNFL. Also, our results are in line with most studies stating that RNFL is thinnest in the temporal quadrant; 20,45 while a few studies report it to be nasal. 46,47 RNFL thickness is believed to correspond with the physiologic neuroretinal rim shape which follows the Inferior-Superior-Nasal-Temporal (ISNT) rule.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the present study, the overall average RNFL thickness and the mean thicknesses in the superior and nasal quadrants were significantly lower in females. Other studies have had conflicting results in terms of gender and RNFL thickness; some studies had results in agreement with ours and some showed no inter‐gender difference. According to the present controversy, it is not possible to comment on the gender‐related difference in RNFL thickness with certainty.…”
Section: Discussionsupporting
confidence: 82%
“…31,32 In addition, the RNFL thickness on the inferior side tends to be slightly thicker than on the superior side in normal subjects. 4,33 However, the superior VF corresponding to the inferior retina is involved more frequently in the early stages of glaucoma, with faster progression than the inferior VF. 34,35 In addition, the inferotemporal meridian was found to be the most frequent location where RNFL progression was detected.…”
Section: Discussionmentioning
confidence: 99%
“…But values obtained with these two analysers have been found to be numerically different. Indeed, with SD-OCT, it has been reported that the mean papillary RNFL thickness in normal individuals ranges from 94.0 to 99.4 μm6 7 whereas with GDx VCC, the mean peripapillary RNFL thickness ranges from 55.26 to 58.59 μm 9 10…”
Section: Introductionmentioning
confidence: 99%